Endodontic treatment of maxillary incisor with dens invaginatus and dens exvaginatus: Case report - Insoon Chang (Journal of Dental Problems and Solutions - Peertechz Publications, 2021)
Dens Invaginatus (DI) and talon cusp are rare dental malformations involving complicated clinical and anatomical features and pose many approaches to managing the case. In this case, lingual caries led to pulp necrosis on tooth #10 with two Type II Oehler's DI chambers with talon cusp. Nonsurgical endodontic treatment was achieved using modern endodontic techniques and material. On the other hand, tooth #7 with Type I Oehler's DI with lingual caries was not associated with pulp pathosis and indicated with a preventative treatment approach.